1998
DOI: 10.1002/(sici)1096-9861(19981116)401:2<217::aid-cne5>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Neurons synthesizing gonadotropin-releasing hormone mRNA subtypes have multiple developmental origins in the medaka

Abstract: The origins of the different populations of gonadotropin-releasing hormone (GnRH)-containing neurons in the brains of two genotypes (HO4C; HNI-II) of medaka Oryzias latipes were analyzed at different stages of development (day 1 after fertilization through adulthood), by using oligonucleotide probes specific to salmon-, seabream-, and chicken II-GnRH mRNA and antisera against specific GnRH peptides. Between the two genotypes, there was no difference in the site and time of GnRH expression or the final pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 39 publications
6
33
3
Order By: Relevance
“…The relatively higher GnRH-II and GnRH-III mRNA levels compared with that of GnRH-I mRNA observed in cobia and seabream (Wong et al 2004) suggests that GnRH-II and GnRH-III could be more important during larval development. The overall increasing trend of GnRH-II and GnRH-III mRNAs during the larval development in cobia is also consistent with the increasing number and size of the GnRH immunoreactive cells reported during early development of other teleosts (Parhar et al 1998, GonzĂĄlez-MartĂ­nez et al 2002.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The relatively higher GnRH-II and GnRH-III mRNA levels compared with that of GnRH-I mRNA observed in cobia and seabream (Wong et al 2004) suggests that GnRH-II and GnRH-III could be more important during larval development. The overall increasing trend of GnRH-II and GnRH-III mRNAs during the larval development in cobia is also consistent with the increasing number and size of the GnRH immunoreactive cells reported during early development of other teleosts (Parhar et al 1998, GonzĂĄlez-MartĂ­nez et al 2002.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, Wong et al (2004) have reported early detection of GnRH receptor, FSHb, FSH, and LH receptors and Vasa mRNAs during the larval development of gilthead seabream using real-time RT-PCR. Therefore, these genes of the hypothalamicpituitary-gonad (HPG) axis may potentially be active much earlier than it has been suggested based on the ISH studies (CambrĂ© et al 1990, Parhar et al 1998. Furthermore, the finding of higher GnRH-I mRNA expression in male cobia undergoing puberty when compared with the juvenile females of the same age is consistent with the designation of GnRH-I as the major regulator of pituitary gonadotropins in all vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In medaka, a species-specific form of GnRH1 has been cloned [36] and it is expressed in the hypothalamus. The differences in timing between the onset of GnRH1 and GnRH3 gene expression led to the proposal that the terminal nerve (GnRH3) and hypothalamic (GnRH1) cells do not share a common origin in the olfactory placode but have separate origins [9,36]. Consistent with this hypothesis, we have found that in zebrafish GnRH3 cells of the terminal nerve and GnRH2 cells of the midbrain (Fig.…”
Section: Gnrh Cellssupporting
confidence: 75%
“…In the chick GnRH1 is first expressed along the neural fold, becomes localized to the anterior neural folds, and subsequently is expressed in bilateral clusters of cells within the most anterior neural folds [61]. In medaka, a species-specific form of GnRH1 has been cloned [36] and it is expressed in the hypothalamus. The differences in timing between the onset of GnRH1 and GnRH3 gene expression led to the proposal that the terminal nerve (GnRH3) and hypothalamic (GnRH1) cells do not share a common origin in the olfactory placode but have separate origins [9,36].…”
Section: Gnrh Cellsmentioning
confidence: 52%
“…Based on recent data from early vitellogenic females (GSI<1%), sGnRH-I mRNA is predominantly expressed in the olfactory bulbs and telencephalon, whereas sGnRH-II mRNA is the most abundant form in the preoptic area and hypothalamus (F FerriĂšre, unpublished observation). However, in teleosts, projection of sGnRH fibres into the pituitary has been shown to originate from preoptic and hypothalamic neurones (Anglade et al 1993, Parhar et al 1998. This is in agreement with the findings of the present study whereby sGnRH-I mRNA was less abundant in the brains of 11-month-old AS(+) immature females, whereas the sGnRH-II form decreased in maturing AS(+) males.…”
Section: Pab-directed Expression Of Inserted Genes In Transgenic Troutmentioning
confidence: 99%